KEMAMPUAN MAHASISWA DALAM MENGANALISIS PUISI “ULAT” KARYA OKA RUSMINI MELALUI PENDEKATAN FEMINIS - Deviana Rahmalia Putri; Fajrina Nur Azizah; Wardatun Nikoyah; Kusuma, Dewi Kusuma (LPPM UNU CIREBON, 2023)
This study examines the ability of students in the city of Cirebon to analyze poetry with feminism in it. The poem that was used as the object of the research was a poem entitled